Little kitten - Doherty, Paula (Igloo Sywell, 2009)
Little Kitten wants to join the other animals, but she doesn't like splashing with the frogs, she can't hop with the bunnies, and she can't fly like an owl. Will she find someone to play with? Join Little Kitten on her journey of discovery